Analisis meta pada manajemen pasca pelatihan untuk meningkatkan produktivitas guru di SMK - I Made Sudana (Jurnal Pendidikan Vokasi, 2011)
META ANALYSIS IN POST TRAINING MANAGEMENT TO IMPROVE TEACHER PRODUCTIVITY IN VOCATIONAL SCHOOLPost in-service training programs of teachers have never been evaluated to investigate their effectiveness and productivity. Some factors are indicated to affect unmeasured productivity of the program: (1) there is no a clear procedure in evaluating productity of in-service training program, (2) there is no standardized procedures to evaluate teacher performance, (3) a complex teachers' background make evaluation instrument is difficult to be developed, (4) trainings have not been based on teachers needs, (5) training content could not be implemented, and (6) monotonous methode were usually employed. However, this research investigated seven advantages: (1) School productivity is improved, (2) relationship between management and staff is in harmony, (3) a faster  decision making is achieved, (4) a high commitment and motivation for school community, (5) to push more open management through implementation of participative managerial, (6) more effective communication, and (7) a functional conflict resolution. The advantages for teacher: (1) help teacher to make a better decision making, (2) to help teacher to solve problems, (3) motivational factors are internalized and operationalized, (4) to develop teacher to improve performance, (5) to help teacher to be a self confidence teacher, (6) to help teacher to acquire intellectual and technical ability, (7) to improve teacher's work satisfaction, (8) more   recognition on individual performance, (9) more independent teachers, and (10) lessen teacher's anxious toface future.